CFD Investigation of Flame and Pressure Wave Propagation through Variable Concentration Methane-Air Mixtures in a Tube Closed at One End. Issue 7 (19th May 2021) - Peng, Zhengbiao; Zanganeh, Jafar; Ingle, Rahul; Nakod, Pravin; Fletcher, David F.; Moghtaderi, Behdad
ABSTRACT: CFD modeling of methane-air combustion and the subsequent flame and pressure wave propagations from the closed end of a detonation tube is presented, with a focus on propagation through variable concentration mixtures. A partially premixed combustion model that avoids the need to specify the flame speed is developed based upon the Flamelet Generated Manifold (FGM) model and needs no tuning to account for different methane concentrations. The numerical model is extensively validated using the experimental data collected from a large-scale detonation tube. The results show that the pressure wave propagation experiences three sequential stages: i) growth; ii) decoupling; and iii) decay. The peak overpressure is generated in the pressure wave growth stage in which the wave front transiently couples with the flame front, and the confined tube walls induce lateral wave reflections and force the flame front to transit from spherical to planar. Subsequently, the wave front starts decoupling from the flame front, with an almost constant global maximum pressure. After decoupling, the global maximum pressure drops because of the energy loss incurred through the wave propagation. The different methane concentrations introduced initially after the explosion chamber containing a stoichiometric mixture do not affect the peak overpressure or the pressure wave propagation but do affect the profile and propagation of the flame. Exponential acceleration of the flame propagation speed is found in the growth stage of pressure wave propagation, followed by the transition to a linear acceleration stage. For cases with the methane concentration becoming smaller than the stoichiometric concentration, the linear flame acceleration rate is smaller, with more pronounced flame stretching.